Research data on volatile organic compounds emitted from upholstered furniture - Chemical Insights Research Institute (20410063) (2025)
Introduction Volatile organic compounds (VOCs) are compounds that have a high vapor pressure and low water solubility, which are emitted from solid or liquid sources. Furniture and building materials are a major source of indoor VOCs, which contribute to the background VOC levels at normal room conditions, and occupants are exposed to these VOCs when indoors. Among the various VOCs, some of them may have short- and/or long-term adverse health effects. Therefore, it is important to understand the VOC emissions from common indoor sources. However, accurate monitoring of VOCs is not available for many researchers and the public. Chemical Insights, a unit of UL Research Institutes, has conducted a research initiative on characterizing VOCs emissions from upholstered furniture during normal use. To increase data transparency and share useful information, these research data are made available to stakeholders such as researchers, educators, and general public who may need indoor VOC source data. Methods Four types of upholstered chairs with different fire-resistant technologies were selected. Emissions from chairs were characterized using validated exposure chamber; an agitation robot was used to mimic a person sitting on the chair.1,2 VOCs were collected on Tenax® TA (60/80 mesh) sorbent tubes and then thermally desorbed and analyzed by thermal desorption-gas chromatography/mass spectrometry (TD-GC/MS) following the US EPA Methods TO-173 and TO-14. Individual VOCs were quantified using multi-point calibration curves with authentic standards if available. Total VOC (TVOC) was the sum of toluene equivalent response in C6 to C16 range. Low-molecular-weight carbonyls (aldehydes) samples were collected on 2,4-dinitrophenylhydrazine (DNPH) cartridges and analyzed using high-performance liquid chromatography (HPLC) following EPA Method TO-11A5. The laboratory quality program enables the accuracy of the identification and quantification of analyzed VOCs and aldehydes. Emission rate of each detected VOC was calculated in unit of µg/h. Details of sampling and analysis methods can be found in peer-reviewed publications.1,2 Database This database includes VOC emissions from upholstered chairs and cushions using different flame retardant technologies that are typically found in residential and commercial buildings. This data provides VOC emission information from different upholstered chair types. Homeowners, builders, designers and facility managers can gain knowledge on VOC emission levels from these furniture sources, which will further guide material selection, planning and design. Please see ULRI_CHAIR_NOTE file for details of data dictionary. Data portal The data portal provides an interactive way of viewing and screening data by selecting the parameters of interest. Users can download the data as needed. References Davis, A.; Ryan, P. B.; Cohen, J. A.; Harris, D.; Black, M. Chemical Exposures from Upholstered Furniture with Various Flame Retardant Technologies. Indoor Air 2021, 31 (5), 1473–1483. https://doi.org/10.1111/ina.12805. Harris, D.; Davis, A.; Ryan, P. B.; Cohen, J.; Gandhi, P.; Dubiel, D.; Black, M. Chemical Exposure and Flammability Risks of Upholstered Furniture. Fire and Materials 2021, 45 (1), 167–180. https://doi.org/10.1002/fam.2907. US EPA. Compendium of Methods for the Determination of Toxic Organic Compounds in Ambient Air Second Edition Compendium Method TO-17 Determination of Volatile Organic Compounds in Ambient Air Using Active Sampling Onto Sorbent Tubes, 1999. US EPA. Compendium of Methods for the Determination of Toxic Organic Compounds in Ambient Air - Second Edition. Compendium Method TO-1 Method for the Determination of Volatile Organic Compounds (VOCs) in Ambient Air Using Tenax® Adsorption and Gas Chromatography/Mass Spectrometry (GC/MS), 1999. US EPA. Compendium of Methods for the Determination of Toxic Organic Compounds in Ambient Air Second Edition Compendium Method TO-11A Determination of Formaldehyde in Ambient Air Using Adsorbent Cartridge Followed by High Performance Liquid Chromatography (HPLC), 1999.